Multiple doping of graphene oxide foams and quantum dots: new switchable systems for oxygen reduction and water remediation. Issue 27 (19th June 2015) - Favaro, M.; Carraro, F.; Cattelan, M.; Colazzo, L.; Durante, C.; Sambi, M.; Gennaro, A.; Agnoli, S.; Granozzi, G.
Abstract : Single- and multi-boron, nitrogen, sulphur doped graphene oxide quantum dots and three-dimensional foams are synthesized by a simple and environmentally friendly electrochemical method. Abstract : Single- and multi-boron, nitrogen, sulphur doped graphene oxide quantum dots and three-dimensional foams are synthesized by a simple and environmentally friendly electrochemical method. The electrochemical activity of these materials in the oxygen reduction reaction is investigated by cyclic voltammetry and rotating disk electrode measurements. The experimental data demonstrate that the reaction selectivity is controlled by the oxidation degree of the materials: as-prepared graphene oxide quantum dots, which present highly oxidized functional groups, follow a two-electron reduction pathway and produce hydrogen peroxide, whereas after a reduction treatment by NaBH4, the same materials favour a four-electron reduction of oxygen to water. The high selectivity and high efficiency of the graphene oxide quantum dots for the production of hydrogen peroxide can be efficiently used for water remediation applications (phenol decomposition).